Human-nature relationship and public perception of environmental hazards along the Maros/Mureş River (Hungary and Romania) - Sipos, György; Blanka-Végi, Viktória; Ardelean, Florina; Onaca, Alexandru; Ladányi, Zsuzsanna; Rácz, Attila; Urdea, Petru (Geographica Pannonica, 2022)
Public participation is increasingly important in flood and environmental management planning. Accordingly, understanding the attitude of local society to natural values and their relations with the environment is highly important to realize successful development projects. This study aimed to analyze the human-nature relationship, the public perceptions of environmental hazards and people's engagement with water management related and human interventions at Maros/Mureş River through a public survey. The survey was carried out in 11 Romanian and Hungarian settlements using the random walking method to interview the local public. The results show that people are a little pessimistic concerning the state of the river, and there are misbeliefs about the general problems affecting its present environmental status. Meanwhile, the perception of flood hazard is governed by the fading memory of the last high-risk flood event in 1970. The engagement of residents is mostly affected by socio-demographic parameters. However, the regularity they visit the river is also very important. Consequently, informing people on apparent environmental issues and processes can greatly help the socially inclusive implementation of water management measures along the river.
Keywords: Maros/Mureş River; public survey; human-nature relationship; human interventions; river and floodplain management